2018
DOI: 10.1515/aoas-2017-0047
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology Considerations for Poultry and Livestock Production Systems – A Review

Abstract: the global animal productivity should proportionally increase to meet the food needs of a growing population. this article presents an overview of the current and promising nano-applications in poultry and livestock production systems that could offer opportunities for improved efficiencies and productivity. some basic information on nanotechnology and the economics of nanotechnology is provided. poultry and animal production systems, current situation and available tools and techniques are presented in parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Such systems can be used for targeted delivery of different cargo molecules [14] to improve drug bioavailability [15], to sustain drug effects in certain target tissues/organs [16], to solubilize drugs, and increase the stability of drugs against degradation [17]. pbENPs, with a mean diameter less than 150 nm, have been shown to possess advantages in delivering antibiotics, hormones, and vaccines for veterinary use [18], and have become an important innovative tool in veterinary science. For veterinary applications in general, it is important that the nanocarrier increase the circulation time of the incorporated active substance, while also ensuring renal elimination [5,19].…”
Section: Introductionmentioning
confidence: 99%
“…Such systems can be used for targeted delivery of different cargo molecules [14] to improve drug bioavailability [15], to sustain drug effects in certain target tissues/organs [16], to solubilize drugs, and increase the stability of drugs against degradation [17]. pbENPs, with a mean diameter less than 150 nm, have been shown to possess advantages in delivering antibiotics, hormones, and vaccines for veterinary use [18], and have become an important innovative tool in veterinary science. For veterinary applications in general, it is important that the nanocarrier increase the circulation time of the incorporated active substance, while also ensuring renal elimination [5,19].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds had significant effects in inducing changes in the composition of the gut as Moyosore et al [31] indicated that the supplement of nanoscale zinc results in a significant rise in the length, width, and surface area of villi, leading to improved digestion and absorption of nutrients. Nano food reduces gut fermentation disorders [32]. Research conducted by Saware et al [33] indicates an increase in the effectiveness of digestive enzymes, especially the α-amylase when using silver and gold nanoparticles in horse food, and this explains the mechanism of the action of these particles in increasing the breakdown of starch to reduce the level of sugar in the large intestine and thus reduce fermentation disorders in the cecum.…”
Section: The Importance Of Nanoparticles In Horse Nutritionmentioning
confidence: 99%
“…Nanomaterials have completely different physical and chemical characteristics compared to the original and raw unmodified chemical forms of selenium (Hartemann et al, 2015), these new characteristics authorize their application in medicinal and nutritional fields (Mohapatra et al, 2014). The success of nanomaterials in many fields contributes to their increased use in poultry industry to enhance productivity, immunity, and combating pathogenic micro-organisms' activity (El Sabry et al, 2018). Nano-selenium has many advantages including high absorption capability, increased surface activity, catalytic efficiency, low toxicity, and reimbursement of the body during oxidative and environmental stressors, as well as alleviate their negative impact (Nasirpour et al, 2017;Purohit et al, 2017).…”
Section: Introductionmentioning
confidence: 99%